Native Appropriation in Sport: Cultivating Bias Toward American Indians - Davis-Delano, Laurel R. (Race and social problems, 2023)
Supporters of American Indian mascots claim that these mascots honor American Indians. If this is the case, then those who have more contact with, and are more supportive of, these mascots would logically demonstrate support for American Indian Peoples in other ways. In this study, we break new ground by employing a cultivation and social learning approach to examine possible associations between greater exposure to American Indian mascots and prejudice toward American Indians, as well as support for their rights. We used an online survey of 903 White Americans to examine associations between long-term exposure to American Indian mascots, attitudes toward Native appropriation, and support for American Indian Peoples. We found that greater exposure to sport media and more contact with American Indian mascots were associated with more prejudice toward and less support for American Indian rights, via double mediators—first via less opposition to American Indian mascots, and second via less opposition to other types of Native appropriation. These findings provide further evidence that American Indian mascots are harmful to American Indians, in this case via their association with higher levels of modern prejudice, less feelings of warmth, and less support for American Indian Nation sovereignty and trust relationship with the United States government. Further, our findings suggest that this harm may be related to lessons learned from the general phenomenon of Native appropriation, which includes acceptance of objectification and dehumanization of American Indians, disregard for their feelings, and legitimation of White settler colonial power.